Phenotypic and Genotypic Identification of Bacteria Isolated From Traditionally Prepared Dry Starters of the Eastern Himalayas - Pradhan, Pooja; Tamang, Jyoti Prakash (Frontiers in Microbiology, 2019)
ABSTRACT Preparation of dry starters for alcohol production is an age-old traditional technology in the Eastern Himalayan regions of east Nepal, Darjeeling hills, Sikkim, and Arunachal Pradesh in India, and Bhutan. We studied the bacterial diversity in 35 samples of traditionally prepared dry starters represented by marcha of Nepal, Sikkim, Darjeeling hills and Bhutan, phab of Bhutan, and paa, pee and phut of Arunachal Pradesh and marcha, respectively. Populations of bacteria in these starters were 105 to 108 cfu/g. A total of 201 bacterial strains were isolated from starters samples and were phenotypically characterized and confirmed the identity by 16S rRNA sanger sequencing method. The dominant phylum was Firmicutes (85%), followed by Proteobacteria (9%) and Actinobacteria (6%), respectively. Lactic acid bacteria (LAB) (59%) formed the most abundant group followed by non-LAB (32%) and Gram-negative bacteria (9%). Based on 16S rRNA gene sequencing result, we identified LAB: Enterococcus durans, E. faecium, E. fecalis, E. hirae, E. lactis, Pediococcus acidilacti, P. pentosaceus, Lactobacillus plantarum subsp. plantarum, Lb. pentosus, Leuconostoc mesenteroides, Weissella cibaria; non-LAB: Bacillus subtilis subsp. inaquosorum, B. circulans, B. albus, B. cereus, B. nakamurai, B. nitratireducens, B. pseudomycoides, B. zhangzhouensis, Kocuria rosea, Staphylococcus hominis subsp. hominis, S. warneri, S. gallinarum, S. sciuri, Lysinibacillus boronitolerans, Brevibacterium frigoritolerans, and Micrococcus yunnanensis; Gram-negative bacteria: Pseudomonas putida, Klebsiella pneumoniae, Enterobacter hormaechei subsp. xiangfangensis, E. hormaechei subsp. steigerwaltii and Stenotrophomonas maltophilia. We characterized diversity indexes of bacterial community present in traditionally prepared dry starters for alcohol fermentation. This is the first report on the bacterial diversity of traditionally dry starters of the Eastern Himalayas by sanger sequencing.